Muhit al-Tavarikh (The sea of chronicles) - Fallazahdeh, Mehrdad. (Studies in Persian Cultural History, 2013)
This study provides a critical edition of chapters nine and ten of Muḥīṭ al-tavārīkh (The Sea of Chronicles) by Muḥammad Amīn born Mīrzā Muḥammad Zamān Bukhārī (Ṣūfīyānī). Muḥīṭ al-tavārīkh is a valuable source for the study of late seventeenth-century Central Asian history, historiography, and language. The present work represents the first critical edition of a primary source of Subḥān Qulī Khān's reign. The ninth chapter ( bāb ) offers accounts of the Timurid kings, Abulkhayrid/Shaybanid and the first four Ashtarkhanid/Janid khans. The tenth chapter presents a detailed account of the life and times of "the last great" Ashtarkhanid/Janid khan, Subḥān Qulī Bahādur (1682-1702), revealing historical information essential for scholars of the period and region.